What Influences the Influenza Vaccination Rate of Canadians? - Pei , Yi (Université d'Ottawa | University of Ottawa, 2014)
Influenza is a common disease not just in Canada but also worldwide that can cause serious health complications. Using data from the 2012 Canadian Community Health Survey (CCHS) data set, this paper explores the individual determinants of the decision to get an influenza vaccination. After dividing the sample into three age groups (young, middle-aged and seniors) and estimating logit models for each age group, this paper finds that being female, having a regular doctor and having certain chronic conditions are positively related to the probability of getting a flu shot for these three age groups. Smoking, living in Newfoundland and Labrador and living in Quebec are negatively related to the probability of influenza vaccination. Also, seniors have higher influenza vaccination rates compared to middle-aged and younger adults.